TECHNIQUE OF ESTIMATION OF ERROR IN THE REFERENCE VALUE OF THE DOSE DURING THE LINEAR ACCELERATOR RADIATION OUTPUT CALIBRATION PROCEDURE. Part 2. Dependence on the characteristics of collimator, optical sourse-distance indicator, treatment field, lasers and treatment couch - Y. V. Tsitovich; I. G. Tarutin; M. G. Kiselev (Приборы и методы измерений, 2016)
To ensure the safety of radiation oncology patients needed to provide consistent functional characteristics of the medical linear accelerators, which affect the accuracy of dose delivery. To this end, their quality control procedures, which include the calibration of radiation output of the linac, the error in determining the dose reference value during which must not exceed 2 %, is provided. The aim is to develop a methodology for determining the error (difference between a measured value of quantity and its true value) in determining this value, depending on the characteristics of the collimator, the source to surface distance pointer, lasers, radiation field and treatment table. To achieve the objectives have been carried out dosimetric measurements of Trilogy S/N 3567 linac dose distributions, on the basis of which dose errors depending on the accuracy setting the zero position of the collimator, the deviation of the collimator rotation isocenter, the sourcesurface distance pointer accuracy, field size accuracy, the accuracy of lasers and treatment table positioning were obtained. It was found that the greatest impact on the value of the error has the error in the optical SSD indication and the error in the lasers position in the plane perpendicular to the plane of incidence of the radiation beam (up to 3.64 % for the energy of 6 MV). Dose errors caused by error in the field size were different for two photon energies, and reached 2.54 % for 6 MeV and 1.33% for 18 MeV. Errors caused by the rest of the characteristic do not exceed 1 %. Thus, it is possible to express the results of periodic quality control of these devices integrated in linac in terms of dose and use them to conduct a comprehensive assessment of the possibility of clinical use of a linear accelerator for oncology patients irradiation on the basis of the calibration of radiation output in case of development of techniques that allow to analyze the influence dosimetric characteristics the radiation beam.